Comparative Analysis On The Silver Recovery Has Saturated Fixer Deposition Using The Method And Naoh Na2s - Jeffri Ardiyanto; Bagus Abimanyu; Agustina Dwi Prastanti (Poltekkes Kemenkes Semarang, 2013)
The purpose of this study was to determine the weight of the silver produced by use of NaOH and Na2S materials. This research is experimental research. Data were collected by precipitating a saturated solution of fixer for silver content taken with the use of NaOH and Na2S each with 2.5 and 5 molarity. The results showed in the first precipitation with 2.5 M NaOH produces silver sediment 15 g and 2.5 g. The deposition of the second with 5 M NaOH produces silver precipitate 49 g and 10 g. Deposition third with 2.5 M Na2S produces silver precipitate 37 g and 6.5 g. Deposition fourth with 5 M Na2S produces silver precipitate 38 g and 8 g. Among the four most widely produced deposition of silver is a concentration of 5 M NaOH were able to produce as much as 10 g of silver.